Control of doping by matrix in few-layer graphene/metal oxide composites with highly enhanced electrical conductivity. (January 2015) - Fan, Yuchi; Kang, Lijing; Zhou, Weiwei; Jiang, Wan; Wang, Lianjun; Kawasaki, Akira
Abstract: Doping of graphene by contacting other materials has significant meaning to the graphene based devices and composites. In this work, highly conducting few-layer graphene (FLG) based composites in which the doping type and level can be manipulated by incorporating FLG with different matrixes are fabricated. Three metal oxides with different level of oxygen vacancies (α-Al2 O3, 3%mol yttria stabilized zirconia (3YSZ) and 8%mol yttria stabilized zirconia (8YSZ)) are selected as matrix material. While the electrical conductivity is largely enhanced to 1.4 × 10 3 –2.1 × 10 3  Sm −1 in the composites by adding 4.42–5.1 vol.% FLG, hole-doping level in composites increases in the sequence of FLG/Al2 O3  < FLG/3YSZ < FLG/8YSZ from room temperature to moderate temperature, as indicated by thermopower measurement and calculation. It is deduced that the concentration of oxygen vacancy on the surface of oxides plays an important role for tuning the hole-doping level in FLG and the control of doping can be realized accordingly.